Ungraying of the Norwegian fishing fleet: turning the tide? - Signe Annie Sønvisen; Jahn Petter Johnsen; Jostein Vik (Frontiers in Sustainability)
The “graying of the fleet” has been a persistent challenge in many fisheries worldwide, with an aging workforce and declining youth participation raising concerns about recruitment and knowledge transfer. However, since 2014–2015, Norway has experienced a reversal of this trend. This paper explores the phenomenon of “ungraying” in the Norwegian fishing fleet. Drawing on survey data and the Fisheries Employment System (FES) theoretical framework, the study finds that recruitment challenges are not widespread and current recruitment patterns reveal a strong reliance on social networks, though formal education is becoming more important. The Norwegian case illustrates how targeted policies, combined with evolving social and economic conditions, can address demographic challenges in fisheries. However, sustaining this trend requires adaptive strategies that balance the need for formal qualifications with mechanisms that maintain community-based engagement, ensuring the long-term vitality of coastal communities and the fisheries. This study contributes to the literature on fisheries recruitment and employment and introduces the Fisher Pathway Model (FPM), which is an analytical framework to capture the evolving FES and the interplay between primary and secondary socialization.